Educational Tools for Sustainable Growth in Science Education: Literature Review - Eksa Nursafira Sunarya; Riandi; Irma Rahma Suwarma (Pedagogia: Jurnal Ilmiah Pendidikan, 2024)
The idea of learning apps for Education for Sustainable Development (ESD) has recently made major strides. However, many people are unsure of what learning applications for ESD are, why they are necessary, and how to utilize them. The literature review on ESD-based science learning applications is so wide that many researchers need more time and a longer process to locate the relevant data sources. This study aims to give a summary or literature review of the significance of ESD-based learning apps for students in schools. The researcher's summary article highlights the fundamental difficulties that must be addressed regarding ESD, the importance of ESD and its application in education, notably in science education, as well as ways for efficiently applying ESD learning applications. ESD-based learning applications constitute a novel technique in the educational field. ESD consists of three major areas: economic, social, and environmental. Integrating ESD into science education is critical to accomplishing the SDGs. Several significant factors in the implementation of ESD learning applications in science in Indonesia include the government (PATK IPA), professional bodies such as the Indonesian Science Educators Association, Science Subject Conferences, and community involvement. The method in this study is qualitative research, specifically content analysis. This study includes a literature review of several periodicals, publications, and textbooks.